2020
DOI: 10.1016/j.isci.2020.101113
|View full text |Cite
|
Sign up to set email alerts
|

Allicin Regulates Energy Homeostasis through Brown Adipose Tissue

Abstract: HIGHLIGHTS Allicin reduces adiposity and maintains glucose homeostasisAllicin activates the brown adipocytes and increases the energy expenditure Allicin enhances BAT activity partly through SIRT1-PGC1a-Tfam signaling pathway Allicin regulates mitophagy via suppressed sirt5-mediated succinylation accumulation

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…In present study, we employed aqueous allicin-rich garlic extract (ARGE), prepared according to a previously reported method with slight modifi cations [33]. Allicin has multiple pharmacological functions, including cholesterol-lowering eff ects [34], browning of WAT [35] and regulates energy homeostasis through BAT activation [19]. Since allicin is a highly reactive volatile compound, it decomposes rapidly in the presence of air.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In present study, we employed aqueous allicin-rich garlic extract (ARGE), prepared according to a previously reported method with slight modifi cations [33]. Allicin has multiple pharmacological functions, including cholesterol-lowering eff ects [34], browning of WAT [35] and regulates energy homeostasis through BAT activation [19]. Since allicin is a highly reactive volatile compound, it decomposes rapidly in the presence of air.…”
Section: Discussionmentioning
confidence: 99%
“…Allicin, one of the bioactive components of garlic has numerous biological functions including anti-obesity eff ects. Allicin administration enhances beiging/ browning of white adipose tissue, modulates gut microbiota and recently has been found to enhance whole-body energy metabolism via brown adipose tissue (BAT) activation [18,19]. Allicin is absent in the raw garlic and is only produced upon crushing of the garlic clove from its odorless precursor alliin through the enzymatic reaction of enzyme alliinase [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been demonstrated that allicin administration to the HFD fed and Db/Db mice significantly increased BAT activity and energy expenditure. In-vitro experiments performed on isolated brown adipose tissues from mice showed that allicin directly activates BAT by upregulating the expression of UCP1 protein(C. Zhang et al, 2020). Cumulatively, these studies suggested the direct effect of TRPA1 agonists for the prevention of obesity by enhancing energy expenditure.…”
Section: Trpa1 In Bat Thermogenesis and Modulationmentioning
confidence: 99%
“…Purple maize extract rich in ferulic acid and anthocyans was found to prevent HFD-induced obesity in mouse models by promoting white fat browning and thermogenesis, while reducing inflammation, partly through upregulation of SIRT1 and AMPK [ 338 ]. Another compound, allicin, regulates energy homeostasis partly through SIRT1/PGC1α; however, at higher concentrations, it leads to mitochondrial problems through SIRT5 inhibition [ 535 ]. The compound 23-epi-25-deoxyactein was found to promote adipocyte lipolysis through AMPK signaling and the SIRT1/FOXO1 pathway, and to reduce body weight gain and fat mass [ 536 ].…”
Section: The Role Of Sirtuins In Metabolic Tissuesmentioning
confidence: 99%